Penerapan Blockchain dalam Sistem Informasi Akuntansi (SIA) - Tio Sinta Marito Br. Marbun; Zahra Adinda (CV. ITTC INDONESIA, 2025)
The scientific paper contains material about how to apply blockchain in transaction activities supported by accounting information systems. This paper aims to examine the benefits and challenges obtained by applying blockchain to accounting information systems. The research method used is the literature review method, namely re-analyzing the results of previous research related to theories, concepts and research result. The findings show that blockchain is able to increase efficiency, transparency and strong security in transaction recording systems. However, blockchain still has challenges in its implementation, such as the limited ability of accountants to use blockchain.